Qualitative analysis of drivers of poka-yoke in small and medium enterprises of Indian automobile sector. (23rd April 2019) - Kumar, Sanjay; Luthra, Sunil; Haleem, Abid; Garg, Dixit
Poka-yoke has been recognised as a proven approach towards achieving 'error free' environment, especially in manufacturing. In this paper, an attempt has been made to justify importance of poka-yoke in SMEs, identify and analyse important drivers for successful implementation of poka-yoke concept. Literature review methodology has been utilised to identify important drivers for successful implementation of poka-yoke concept in SMEs of Indian automobile. Analytical hierarchy process (AHP) methodology has been used for the ranking of identified drivers. 'Management attitude' driver has been identified as top ranked driver to responsible to implement poka-yoke in Indian automobile SMEs. Further, DEMATEL methodology has also been used to understand and categorise these identified drivers of poka-yoke implementation into cause group and effect group of drivers. This paper may help production engineers and managers to identify errors and further rectify them for gaining competitive advantage over domestic and international automobile market players.